A Radiomics Nomogram for Non-Invasive Prediction of Progression-Free Survival in Esophageal Squamous Cell Carcinoma - Yan, Ting; Liu, Lili; Yan, Zhenpeng; Peng, Meilan; Wang, Qingyu; Zhang, Shan; Wang, Lu; Zhuang, Xiaofei; Liu, Huijuan; Ma, Yanchun; Wang, Bin; Cui, Yongping (Frontiers in Computational Neuroscience, 2022)
Abstract To construct a prognostic model for preoperative prediction on computed tomography (CT) images of esophageal squamous cell carcinoma (ESCC), we created radiomics signature with high throughput radiomics features extracted from CT images of 272 patients (204 in training and 68 in validation cohort). Multivariable logistic regression was applied to build the radiomics signature and the predictive nomogram model, which was composed of radiomics signature, traditional TNM stage, and clinical features. 21 radiomics features were selected from 954 to build a radiomics signature which was significantly associated with progression-free survival (PFS) (p<0.001). The area under the curve of performance was 0.878 (95% CI: 0.831-0.924) for the training cohort and 0.857 (95% CI: 0.767-0.947) for the validation cohort. The radscore of signatures’ combination showed significant discrimination for survival status. Radiomics nomogram combined radscore with TNM staging showed considerable improvement over TNM staging alone in the training cohort (C-index, 0.770 vs 0.603; p<0.05), and it is the same with clinical data (C-index, 0.792 vs 0.680; p<0.05), which were confirmed in the validation cohort. Decision curve analysis showed that the model would receive a benefit when the threshold probability was between 0 and 0.9. Collectively, multiparametric CT-based radiomics nomograms provided improved prognostic ability in ESCC.